Green Internet of Things (IoT) Solar Photovoltaic Absorption Optimization Based Panel Orientation in East Malaysia - Chew, Kim Mey; Daniel Chia, Wei Fung; Yiiong, Siew Ping; Syvester Tan, Chiang Wei (2023)
The development of Internet of Things (IoT) technology and its integration into smart cities have transformed the way people work and live while enriching civilization. However, IoT technologies pose a range of challenges in smart cities, including increased energy consumption, hazardous contamination and e-waste. Smart City applications need to be environmentally responsible, which requires a shift to green IoT. Consequently, tactics and strategies aimed at reducing pollution threats, traffic waste, resource use, energy use, public safety, quality of life, environmental sustainability, and cost management should be taken into consideration. Past researches have been initiated to study the efficiency of solar energy as an alternative energy source for IoT. An IoT system has been developed to monitor the effectiveness of solar panels and identify factors that may influence its effectiveness. This article addresses the optimisation of photovoltaic absorption when polycrystalline and monocrystalline solar panels are used for comparative purposes to determine which panel is more efficient. In this study, the panels were exposed to sunlight for at least 12 hours per day and oriented south and north respectively to obtain the optimal position. The results showed that the power generated by the monocrystalline (0.3A) is greater than the polycrystalline solar panels (0.25A). The intensity of sunlight for the country (Malaysia) in the northern hemisphere is expected to be greater in the south. But the result showed a slightly higher light intensity in the north. The phenomenon was explained and the solar panels located in East Malaysia were recommended to be turned according to the optimum monthly tilt-angle change.